PENGARUH KOMPETENSI, PROFESIONALISME, DAN PENGALAMAN AUDIT TERHADAP KEMAMPUAN AUDITOR BADAN PEMERIKSA KEUANGAN (BPK) DALAM MENDETEKSI FRAUD DENGAN TEKNIK AUDIT BERBANTUAN KOMPUTER (TABK) SEBAGAI VARIABEL MODERASI - Didi atmaja (Media Riset Akuntansi, Auditing & Informasi, 2016)
The objectives of this research to empirically analyze the influence of competency, professionalism, and audit experience on The Supreme Audit Institution’s auditor ability of fraud detection with Computer Assisted Audit Techniques (CAATs) as The Moderating Variable. The result showed that The Professionalism, Audit Experience, and CAATs have a positive impact on auditor’s ability of fraud detection. The result also showed that The Audit Experience with CAATs as The Moderating Variable weaken on Auditor’s Ability of Fraud detection. Value of the coefficient of determination indicates that together contribute to dependent variable (Auditor’s Ability of Fraud Detection) of 55,9% . Key words : Competency, Professionalism, Audit Experience, CAATs, and Fraud